Critical Success Factors in Public-Private Partnership - Sri Mulyani (Journal of Accounting Auditing and Business, 2021)
Public Private Partnership (PPP) is an alternative solution for the government in order to provide public goods and services that the government cannot fulfill itself due to budget constraints.    However, not all PPP implementations are successful. In this article, the determinants of the success of PPP implementation are examined.  The analysis was carried out based on articles discussing the keys success factors of implementing PPP. These articles are taken from articles published in reputable journals. The results of the analysis show that organizational factors, interactional factors, structural factors and external factors are the key factors for the success  of the implementation of PPP.